2015
DOI: 10.12998/wjcc.v3.i3.322
|View full text |Cite
|
Sign up to set email alerts
|

Intraparotid facial nerve schwannoma: A case report

Abstract: Facial nerve schwannoma occurring within the parotid gland is a rare tumour. We report a case of schwannoma within the parotid gland in a young female patient, who underwent ultrasound and magnetic resonance imaging (MRI) and subsequent surgical excision of the lesion. The lesion showed hyperintensity on T2-weighted and diffusion-weighted MRI. There was no adjacent lymphadenopathy. Although hyperintensity on diffusion-weighted MRI could suggest malignant tumours, the characteristic "string sign" provided the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…2,7 USG findings in our case were also similar. CT scan is not diagnostic as mentioned by various authors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…2,7 USG findings in our case were also similar. CT scan is not diagnostic as mentioned by various authors.…”
Section: Discussionsupporting
confidence: 84%
“…However, our CT scan findings of a well-defined heterogenous enhancing lesion with multiple cystic areas and mild increased vascularity were also reported by M. Irfan et al and Schwan T Joseph et al 8,9 Authors have suggested a target sign for neurogenic neoplasm. 7,8 MRI with gadolinium is the study of choice for imaging the parotid for suspected nerve lesions. 10 A multitude of parotid tumor will display identical features on imaging including parotid duct cysts, Warthin's tumor and cystadenoma.…”
Section: Discussionmentioning
confidence: 99%
“…4 Intratemporal facial nerve schwannoma presents as a nerve dysfunction in the form of facial paresis while extratemporal nerve involvement presents as a parotid mass without nerve dysfunction. 5 There are no definite radiological findings of intraparotid schwannoma.6 MRI is the radiological test of choice for detecting facial nerve schwannoma. The most common signs are a mass with signal intensity isointense to muscle on T1 and hyperintense to muscle on T2 sequence, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatively it is difficult to diagnosis and differentiates the intraparotid FNS from other parotid tumors, because its low prevalence and very few typical clinical and radiological signs associated with it. On Ultrasonography, schwannoma appear as a cystic mass with internal septations [14,15]. On computed tomography scan, the appearance of schwannoma in the parotid, is a smooth and well circumscribed lesion; and it may revealed the osseous changes [16].…”
Section: Discussionmentioning
confidence: 99%